Застосування інтелектуальної системи INDICO DATA у цифровій медіаінфраструктурі наукового видавництва - Нерода, Т. В.; Мороз, Р. (ТОВ «Видавництво Ліра-К», 2025)
The use of the Indico data intelligent system in the process of optimizing the management of scientific conferences is examined. The capabilities of the system and its functional components are examined. The system allows you to optimize the processing of editorial materials and improves the efficiency of working with manuscripts.
Keywords: наукове видавництво; медіаінфраструктура